Impact of Ramadan fasting on physiological response and sustainable performance in elite athletes. - Singh, Rabindarjeet (Universiti Sains Malaysia, 2013)
During the Islamic holy month of Ramadan, every able-bodied Muslims engage in the practice of fasting, including athletes. Muslims athletes have to compete and/or train during the Ramadan month. There are three considerations when training during the Ramadan period: possibly low levels of fuel (i.e. muscle glycogen stores) within the body, dehydration and feelings of lethargy during the daytime which are due to the acute lack of food and fluid intake as well as loss of sleep time, respectively. It has been argued that these three elements associated with fasting may have a negative impact on exercise or training quality during the Ramadan month.